EXTRACT OF COCOR BEBEK (KALANCHOE PINNATA) AS A CORROSION INHIBITOR (Universitas Negeri Semarang, 2017)
In this study, Cocor Bebek leaves (Kalanchoe pinnata) extract is studied for metal corrosion inhibitor. 10.3 kg of K. Pinnata leaves produce concentrated extract of methanol, n-hexane and ethyl acetate as much as 65.7442, 36.1452, and 15.2711 g respectively. The concentrated extracts were then used to determine the rate of corrosion. Corrosion rate test showed that extract of ethyl acetate can reduce corrosion rate of carbon steel in NaCl 3.5% from 2.954 mpy to 0.963 and 0.923 mpy using 500 ppm and 1000 ppm of extract consecutively. Corrosion rate of Cocor Bebek extract at addition of 500 ppm ethyl acetate in the solution of NaCl 3.5% is decreasing immediately. It was found that the carbon steel corrosion rate decrease as much 4.857 for 6 hours and continuously shows sharp decline until 24 hours of corrosion time. Corrosion rate is slowly decreasing till reach 1.694 mpy at corrosion time of 168 hours.